The complete mitochondrial genome of the Pieris napi (Lepidoptera: Pieridae) and its phylogenetic implication. Issue 3 (2nd July 2020) - Yu, Hong; Shi, Min-Rui; Xu, Jin
Abstract: In this study, the mitochondrial genome (mitogenome) sequence of Pieris napi is determined using next-generation sequencing. The entire mitogenome genome is determined to be 15, 178 bp in length. It contains 37 genes, including 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), and an adenine (A) + thymine (T)-rich region. The overall GC content of the genome is 19.9%. A phylogenetic tree reconstructed by 22 mitogenomes reveals that P. napi is most closely related to Pieris melete .